1998
DOI: 10.1046/j.1365-2141.1998.00802.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of platelet FcγRIIA polymorphism in refractory idiopathic (immune) thrombocytopenic purpura

Abstract: Summary. FcgRIIA, a low affinity receptor for IgG, is a polymorphic molecule: FcgRIIA-HH131, FcgRIIA-HR131 and FcgRIIA-RR131. This polymorphism influences the efficiency of the receptor to bind with IgG2. Recent reports on altered distribution amongst individuals with heparininduced thrombocytopenia (HIT) prompted us to examine the FcgRIIA polymorphism in a cohort of patients with refractory idiopathic (immune) thrombocytopenic purpura (ITP), in whom severe disease had required them to undergo splenectomy. 29 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 13 publications
0
33
4
Order By: Relevance
“…Among adult patients with refractory idiopathic thrombocytic purpura, relative enrichment of Fc␥RIIA-R131/R131 genotype was observed. These findings suggest that impaired processing of immune complexes underlies the pathogenesis of idiopathic thrombocytic purpura [35].…”
Section: Fc␥r Polymorphism and Autoimmune Diseasesmentioning
confidence: 97%
“…Among adult patients with refractory idiopathic thrombocytic purpura, relative enrichment of Fc␥RIIA-R131/R131 genotype was observed. These findings suggest that impaired processing of immune complexes underlies the pathogenesis of idiopathic thrombocytic purpura [35].…”
Section: Fc␥r Polymorphism and Autoimmune Diseasesmentioning
confidence: 97%
“…It has been found that expression of Fcγ receptors on macrophages was higher in ITP patients than healthy controls. With this finding, it has been hypothesized that the presence of this polymorphism might affect the severity and chronicity of thrombocytopenia [9]. …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore in the RR131 group, the male patients were older than the female patients. It is also known that among adults, ITP is more frequent in young women, 70% of female patients being under 40 years of age (George et al, 1994 (Williams et al, 1998; Table 5). …”
Section: Genetic Polymorphism Of Platelet Fcγriia In Thrombocytopeniamentioning
confidence: 99%
“…Both automated DNA sequence analysis and a single-strand conformation polymorphism assay have been used after polymerase chain reaction (PCR) amplification of a 278-base pair (bp) FcγRIIA-specific fragment (Reilly et al, 1994). The method used after FcγRIIA-specific PCR amplification, allele-specific oligonucleotide hybridisation is probably the most widely used, since it was first introduced as an easily adaptable genotyping method (Osborne et al, 1994;Brandt et al, 1995;Burgess et al, 1995;Salmon et al, 1996;Williams et al, 1998). Bachelot et al (1995) used denaturing gradient gel electrophoresis and DNA sequencing of single-strand templates.…”
Section: Typing Of Fcγriia Polymorphism H131rmentioning
confidence: 99%